OPTIMASI WAKTU DAN BIAYA PADA PROYEK A DENGAN METODE CPM DAN PERT DI PT. XYZ - Reni Wulandari (2020)
PT. XYZ is an association of several companies engaged in the field of housing development. The company has completed many housing projects and there are some projects being carried out. The company is always required not to experience tardiness in completing a project. Therefore, as the antisipation of tardiness, optimization of time and cost have to do through the acceleration of implementation by CPM and PERT method, and Linear Programming. The acceleration in the Project A uses three alternatives, that are by adding two work hours of overtime, three work hours of overtime, and four work hours of overtime. The data that is used are the primary data is taken from interview process and the secondary data is taken from related documents included RAB, Schedules, SPK, and others. The time of normal project is around 90 days with a normal cost Rp. 351.337.241. The result of Crashing analysis produces the optimum result for the acceleration of the project completion by adding four work hours of overtime during 76 days with total cost Rp. 373.248.447. The result of Linear Programming analysis produces the optimum time in total 77 days with total cost Rp. 404.604.628.